Can self-reported dieting and dietary restraint identify underreporters of energy intake in dietary surveys? - Rennie, K; Siervo, M; Jebb, SA (2006)
Underreporting is endemic in most dietary studies and ways to reliably identify individuals who may underreport energy intake are needed. Whether questions on self-reported dieting and dietary restraint, in addition to weight status, would identify individuals who may underreport energy intakes was examined in a United Kingdom representative survey. Mean daily energy intake was calculated from the 7-day dietary record of 668 men and 826 women. Reported physical activity was used to assign each subject's activity level and to calculate estimated energy requirements from published equations. Underreporting was calculated as estimated energy requirements minus energy intake with adjustment for daily variation. The Dutch Eating Behavior Questionnaire assessed dietary restraint. Underreporting was higher in men and women reporting current dieting than nondieters (P<0.001) and higher in high-restrained (P<0.001) than low-restrained. When stratified by body mass index category, in men these associations were only significant in the overweight (P<0.001). Dieting was associated with greater underreporting in both lean (P<0.01) and overweight women (P<0.001). Underreporting was higher in lean high-restrained women than low-restrained (P=0.02), but similar in overweight women regardless of restraint score. Questions to assess dietary restraint and current dieting may be useful tools to identify and evaluate underreporting at an individual level in dietary surveys.